(untitled) (Baghdad Science Journal, 2015)
Flow-injection (FI) spectrophotometric method has been developed for the analysis of thymol in pharmaceutical preparations. The method is based on organic coupling reaction between thymol and 4-amino antipyrine in the presence of alkaline medium to form an intense stable red color complex with copper nitrate that has a maximum absorption at 490 nm. Optimum conditions for determination of the drug was investigated .The calibration graph was linear over the range of 5-500 µg.ml-1 of thymol . The limit of detection (LOD) and limit of quantification (LOQ) were 1.81 ?g mL-1 and 3.60 ?g mL-1 respectively .The proposed method was applied satisfactorily to the determination of thymol in mouth wash preparations. The procedure is characterized by its simplicity, accuracy and precision.